Estimation of urinary aldosterone using thin-layer chromatography and fluorimetry. Issue 12 (December 1993) - Mattingly, D; Martin, H; Tyler, C M
Abstract : AIMS–To develop a fluorimetric method for the estimation of urinary aldosterone; to establish a normal range in 24 hour and overnight urine samples; and to investigate the use of overnight urines for detecting hyperaldosteronism. METHODS–Essential steps include hydrolysis of the 18 conjugate to release aldosterone and its oxidation with Benedict's solution, followed by thin-layer chromatography on silica gel and development of fluorescence on the plate with sulphuric acid. RESULTS–There was a linear correlation between the amount of aldosterone and the area under the peak on the chromatogram. The mean intra-assay and interassay coefficients of variation were 4.4% and 6.8%, respectively. The mean aldosterone excretion in 67 adults was 15.7 (SD 8.1) nmol/24 hours. The mean overnight excretion in 65 adults was 2.6 (1.4) nmol/8 hours. The method detected raised concentrations in patients with primary and secondary aldosteronism. CONCLUSIONS–This technique provides an accurate means of assaying urinary aldosterone. Overnight estimations seem to be as effective as 24 hour assays for identifying patients with hyperaldosteronism.